2012
DOI: 10.1146/annurev-resource-110811-114523
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Indirect Land Use Change with Biofuels: Implications for Policy

Abstract: The indirect land use change (ILUC) effect of biofuels has called into question the greenhouse gas (GHG) mitigation benefit of biofuels compared with that of fossil fuels. This article reviews the various economic modeling approaches being used to assess the ILUC effect and discusses the key factors that influence estimates of its magnitude. We find that there is considerable variability in the magnitude of ILUC associated with a biofuel pathway across studies and within a study, depending on underlying model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 46 publications
2
54
0
Order By: Relevance
“…Khanna & Crago (54) report that recent studies found an ILUC effect that is significantly lower than the initial estimate from Searchinger et al (44) of 104 g CO 2 e per MJ (with a range of 20-200 g CO 2 e per MJ). Searchinger et al (44) found that diverting 12.8 million ha of corn cropland to increase US corn ethanol production by 56 billion L would require 10.8 million ha of additional land to be brought into production globally.…”
Section: Multistudy Reviewsmentioning
confidence: 75%
“…Khanna & Crago (54) report that recent studies found an ILUC effect that is significantly lower than the initial estimate from Searchinger et al (44) of 104 g CO 2 e per MJ (with a range of 20-200 g CO 2 e per MJ). Searchinger et al (44) found that diverting 12.8 million ha of corn cropland to increase US corn ethanol production by 56 billion L would require 10.8 million ha of additional land to be brought into production globally.…”
Section: Multistudy Reviewsmentioning
confidence: 75%
“…This approach differs from those based on elasticities, where the researcher exogenously specifies the ease with which land can be substituted among different uses under both the benchmark and the experimental scenarios. Thus, extreme changes in climatic conditions that in fact can drastically alter the suitability of a specific region for producing a given crop may not result in a significant change in the extent of its cultivation and may even show an expansion of the cropland devoted to the crop to compensate for the productivity losses associated with the changing climatic conditions [11]. The Armington trade elasticities are likewise expected to provide exogenous quantification of the ease with which regions substitute imported commodities for domestically produced ones.…”
Section: Land Use Change Responsesmentioning
confidence: 99%
“…An important drawback of trade elasticities is that they take existing trade patterns, rather than ones based on comparative advantage, as their starting point; consequently, countries continue to import from virtually all the same sources even when regional production conditions change radically [1]. In addition, the value assigned to the land elasticity parameter cannot be measured directly and is (at best) inferred from relationships that held in other times and places [11] rather than letting factors such as projected gains or losses in productivity related to changing climatic conditions determine the optimal uses of land.…”
Section: Introductionmentioning
confidence: 99%
“…This combination of factors may have contributed to the considerable variation in regulatory schemes that address LUC-GHG emissions. Possibly as a response to this uncertainty, estimation of LUC-GHG emissions from the production of feedstock for biofuels has become a significant focus of research while debate on policy inclusion continues [19][20][21].…”
Section: Introductionmentioning
confidence: 99%